Outcome of Corticosteroid Injection in patients with plantar fasciitis. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the outcome corticosteroid injection in reducing the intensity of pain in patients with plantar fasciitis.Methods: This was a descriptive study conducted in Department of Orthopaedics, Jinnah Post Graduate Medical Centre (JPMC), Karachi, Pakistan from 1st January 2018 to 1st January 2020.All patients with plantar fasciitis meeting the inclusion criteria were injected single injection of Triamcinolone in the heel and followed in the OPD at two weeks, four weeks and twelve weeks interval. Outcome was assessed in terms of pain reduction as measured with Visual analog scale (VAS).Results: The total number of patients were 50. The mean age   was 41.83 ± 14.07 years. Male patients were 27(54%) while female patients were 23(46%). The mean pre injection VAS improved from 5.41±3.1 to 1.3±7 post injection (P=0.03).Conclusion: Plantar fasciitis treated with single injection of corticosteroid injection resulted in significant pain reduction.